Resources and Governance in Sierra Leone's Civil War. Issue 2 (1st February 2017) - Voors, Maarten; Van Der Windt, Peter; Papaioannou, Kostadis J.; Bulte, Erwin
Abstract: We empirically investigate the role of natural resources, and governance in explaining variation in the intensity of conflict during the 1991–2002 civil war in Sierra Leone. As a proxy for governance quality we exploit exogenous variation in political competition at the level of the chieftaincy. As a proxy for resources we use data on the location of pre-war mining sites. Our main result is that neither governance nor resources robustly explains the onset or duration of violence during the civil war in Sierra Leone.